Adverse Perinatal Outcome in Subsequent Pregnancy after Stillbirth by Placental Vascular Disorders - Monari, Francesca (PLoS One, 2016)
OBJECTIVE: To evaluate outcome in the pregnancy following a stillbirth (SB) by a placental vascular disorders. STUDY DESIGN: A prospective, observational, multicenter study was conducted in woman with a history of stillbirth (> 22 weeks) between 2005 and June 2013, in 3 Italian University Hospitals. Causes of SB were previously identified after extensive investigations. Pregnant women were enrolled within the first trimester. The main outcome was “adverse neonatal outcome”, including perinatal death, fetal growth restriction, early preterm birth <33+6 weeks, hypoxic-ischemic encephalopathy, intracranial hemorrhage or respiratory distress. RESULTS: Out of 364 index pregnancies, 320 women (87.9%) had a subsequent pregnancy during the study period. Forty-seven had an early pregnancy loss. Out of 273 babies, 67 (24.5%) had an adverse perinatal outcome, including 1 SB and 1 early neonatal death (3.7/1000). Women who had a SB related to placental vascular disorders (39.6%), were at higher risk of an adverse neonatal outcome compared with women whose SB was unexplained or resulted from other causes (Adj. OR = 2.1, 95%CI: 1.2–3.8). Moreover, also obesity independently predicts an adverse perinatal outcome (Adj OR = 2.1, 95%CI: 1.1–4.3). CONCLUSION: When previous SB is related to placental vascular disorders there is a high risk for adverse neonatal outcomes in the subsequent pregnancy. Maternal obesity is an additional risk factor.